The relapse of coronary artery disease in patients with diabetes mellitus at Dr. Ramelan Navy Hospital, Surabaya, Indonesia - Priyo Mukti Pribadi Winoto; Ahsan Ahsan; Tina Handayani Nasution (AOSIS, 2019)
The patients with coronary artery disease are susceptible to experience the relapse so that the control towards the risk factors of coronary artery disease is needed such as a history of hypertension, dyslipidemia, suffering from diabetes mellitus, medication adherence, and history of obesity. This study aimed at knowing the relationship between the risk factor of diabetes mellitus and the relapse of coronary artery disease. This study was an analytical observation by using retrospective cohort. The total respondent was 189 people taken by using purposive sampling technique. The finding showed that nearly all patients (82.5%) did not suffer from diabetes mellitus, and most of them (72.5%) experienced the relapse of CAD. The result of the chi-square analysis showed that the p-value of 0.009 < α = 0.05, indicating a significant relationship between Diabetes Mellitus and the relapse of coronary artery disease. The patient with diabetes mellitus has a higher risk of experiencing the relapse of CAD. The nurse should concern and control the risk factors of coronary artery disease that affects the relapse.